PENGARUH KUALITAS PRODUK, PROMOSI, DAN PERSEPSI HARGA TERHADAP LOYALITAS KONSUMEN GERAI AYAM GORENG - Lina Affifastuholihah; Solehatin Ika Putri; Arum Wahyuni Purbohastuti (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the influence of product quality, promotional activities, and price perception on consumer loyalty at fried chicken outlets. The research approach used was quantitative with a survey method. Data were collected through a structured questionnaire from 150 consumers who had made at least two purchases at the fried chicken outlets that were the object of the study. The data analysis technique used multiple linear regression to determine the partial and simultaneous effects of product quality, promotion, and price perception on consumer loyalty. The results showed that product quality, promotion, and price perception had a positive and significant effect on consumer loyalty, both simultaneously and partially. Among the three variables, product quality was the most dominant factor in shaping consumer loyalty, while promotion and price perception strengthened consumers' intentions to make repeat purchases and recommend fried chicken outlets to others. These findings provide implications for fried chicken outlet management to prioritize product quality consistency, supported by targeted promotional strategies and pricing that is perceived as fair by consumers.